2011
DOI: 10.1158/0008-5472.sabcs11-p5-06-08
|View full text |Cite
|
Sign up to set email alerts
|

P5-06-08: Mesenchymal Stem Cells and Carcinoma-Associated Fibroblasts Sensitize Breast Cancer Cells in 3D Cultures to Kinase Inhibitors.

Abstract: Background: Bone-derived mesenchymal stem cells (MSCs) are attracted to cancer lesions and may differentiate to CAFs. By interacting with cancer cells, MSCs and CAFs may promote cancer progression and modulate drug sensitivity. Material and Methods: To analyze ability of MSCs and CAFs to modulate drug response, we generated spheroids of MCF-7 or MDA-MB-231 breast cancer cells in the absence or presence of human (h) MSCs or hCAFs and tested the susceptibility of the breast cancer cells to three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…15,40 The presence of MSCs in the TME also increases the sensitivity of CCs to anti-cancer drugs. 41 The MSC : CC ratio is also critical for any outcome, including changes in CC invasiveness and tumor progression. 18,26 To mimic the complexity of the TME, we encapsulated MSCs in the shell of the construct, which was designed to be in direct contact with the core (representing the cancer site) containing the encapsulated CCs.…”
Section: Cancer Cell Invasion and Protein Expression In The Presence Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…15,40 The presence of MSCs in the TME also increases the sensitivity of CCs to anti-cancer drugs. 41 The MSC : CC ratio is also critical for any outcome, including changes in CC invasiveness and tumor progression. 18,26 To mimic the complexity of the TME, we encapsulated MSCs in the shell of the construct, which was designed to be in direct contact with the core (representing the cancer site) containing the encapsulated CCs.…”
Section: Cancer Cell Invasion and Protein Expression In The Presence Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In a different approach, Dittmer also evaluated if the presence of MSCs in MCF‐7 and MDA‐MB‐231 spheroids affected their susceptibility to 4 tyrosine kinase inhibitors. The interesting results that were obtained indicate that in both spheroids (MCF‐7:MSCs and MDA‐MB‐231:MSCs), the effect of the administered therapeutic anti‐cancer drugs was augmented, pinpointing the decreased resistance to alterations in ERK1/2 phosphorylation and PKCα …”
Section: Cancer‐mscs Co‐culture Relevance In 3d In Vitro Tumor Modelsmentioning
confidence: 99%
“…Regarding the available studies, in most circumstances MSCs exert a positive influence in cancer progression, either by increasing malignant cells proliferation, migration, invasion, drug resistance, and/or cancer stem cell proliferation. Alternatively, only few studies report MSCs as having negative effects in cancer cells . The report by Dittmer and co‐workers, demonstrated that BM‐MSCs can invade MCF‐7 and MDA‐MB‐231 breast cancer 3D aggregates, originating a disorganized structures by disrupting cell–cell adhesion, mainly through E‐cadherin cleavage and nuclear translocation, without however increasing EMT and ERK1/2 activity.…”
Section: Cancer‐mscs Co‐culture Relevance In 3d In Vitro Tumor Modelsmentioning
confidence: 99%
“…Particularly, CAFs play critical roles in resistance to targeted therapeutics such as tamoxifen and Gefitinib (15,16). Beyond their contribution to chemo-, endocrine-, and targeted therapy-resistance, CAFs have been implicated in treatment failure and associated poor clinical outcomes following radiotherapy.…”
Section: Introductionmentioning
confidence: 99%